2019
DOI: 10.1177/1557988319895141
|View full text |Cite
|
Sign up to set email alerts
|

Acute Hepatitis A Outbreak Among Men Who Have Sex With Men in Krakow, Poland; February 2017–February 2018

Abstract: Since February 2017 in Poland, an increasing number of acute hepatitis A (AHA) cases have been reported; a noteworthy increase to 3,072 cases of AHA in 2017 compared to 35 cases in 2016 was reported by the National Institute of Public Health (NIPH). The aim of this study was to evaluate the demographic features, clinical manifestations, laboratory results, and sexually transmitted coinfections. All cases of AHA diagnosed between February 2017 and February 2018 at the University Hospital in Krakow were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Finally, our analysis does not consider how patient portals may also be used to convey information effectively for public health control of Hepatitis A outbreaks occurring globally among SMM and its connection to fecal-oral transmission. Conversations disclosing testing could easily translate to disclosing Hepatitis A and B (HAV, HBV) vaccinations [54][55][56][57]. SMM are recommended to be vaccinated for HAV and HBV [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our analysis does not consider how patient portals may also be used to convey information effectively for public health control of Hepatitis A outbreaks occurring globally among SMM and its connection to fecal-oral transmission. Conversations disclosing testing could easily translate to disclosing Hepatitis A and B (HAV, HBV) vaccinations [54][55][56][57]. SMM are recommended to be vaccinated for HAV and HBV [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…It showed how useful were the different innovative ways in promoting the vaccine in MSM, notably the use of pop-up messages through gay-dating apps in addition to the invaluable role of the community-based organizations [ 26 , 27 ]. While many authors recommended to improve communication toward MSM and to expand access to vaccine during the outbreak [ 18 20 , 24 28 ], vaccine offer during outreach campaigns e.g. at sexual venues or in mobile clinics, has been rarely documented [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, an outbreak extensively affected MSM throughout Europe [ 18 24 ]. Early publications reported that three HAV strains of genotype IA (genotype sequences VRD_521_2016, RIVM-HAV16–090 or V16–25801) circulated in several European Union/ European Economic Area (EU/EEA) member States since June 2016 [ 25 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The last outbreak of HAV infection in Europe and North America among MSM and HIV infected individuals should increase awareness among health care professional that infections can be spread by sexual contacts as well [ 22 ]. The vaccination against HAV should be routinely offered among MSM, bisexual, transgender as well as heterosexual with risky sexual behaviors [ 12 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%